PEMANFAATAN MEDIA INTERAKTIF DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG LINGKUNGAN GEOGRAFIS DAN INTERAKSI SOSIAL DI SEKOLAH DASAR: PEMANFAATAN MEDIA INTERAKTIF DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG LINGKUNGAN GEOGRAFIS DAN INTERAKSI SOSIAL DI SEKOLAH DASAR - Innayah Wulandari (Universitas Muhammadiyah Surabaya, 2025)
Abstract This study aims to analyze the effectiveness of using interactive media in learning Social Studies (IPS) to improve students' understanding of the geographical environment and social interaction in elementary school. The research method used is an experiment with a quasi-experimental design, where there is an experimental group that uses interactive media (Wordwall and learning videos) and a control group that uses conventional methods (lectures and textbooks). The results of the study showed that the use of interactive media significantly improved students' understanding compared to conventional methods. Students in the experimental group showed increased understanding in identifying the geographical environment, understanding the influence of the environment on society, and describing forms of social interaction. In addition, students became more active, enthusiastic and engaged in learning. Statistical tests showed significant differences between the experimental and control groups, proving that interactive media is more effective in improving social studies learning outcomes in elementary schools. Keywords: Interactive Media, Social Studies Learning, Geographical Environment, Social Interaction, Elementary School, Wordwall, Learning Video